Gastropods Diversity in the Mangrove Ecosystem of Kalanganyar River, Kalianyar Village, Bangil, Pasuruan - Kautsar, Ghinahilmi Najalin; Ambarwati, Reni; Rahayu, Dwi Anggorowati (RUMPHIUS, 2026)
Mangrove ecosystems are very important habitats for various organisms, including gastropods, which function as primary decomposers in the ecological cycle. This study aims to identify the diversity of gastropod species in the mangrove area along the Kalanganyar River, Kalianyar Village, Bangil, Pasuruan. Samples were collected randomly around mangrove roots, followed by morphological identification and species classification. The results showed that there were five gastropod species from four families, namely Pirenella cingulata, Telescopium telescopium, Sermyla riquetii, Neripteron violaceum, and Ellobium sp. The Shannon-Wiener diversity index (H') of 1.165 indicates a moderate level of diversity, with Pirenella cingulata as the most dominant species. Water quality tests showed that copper (Cu) levels were still below the threshold, but lead (Pb) levels exceeded seawater quality standards. These results indicate that the mangrove ecosystem is fairly stable, although there are environmental pressures that need to be addressed, particularly those related to heavy metal pollution.